Fracture failure analysis of freeze–thawed granite containing natural fracture under uniaxial multi-level cyclic loads. (December 2020) - Wang, Y.; Li, C.H.; Liu, H.; Han, J.Q.
Highlights: Nature fracture aperture impacted by its physical characteristics subjected F-T. Dynamic mechanical properties are controlled by initial natural fracture volume. Low frequency AE signals increase with increasing natural fracture volume. Rock failure changes from tensile to shear mode with increasing natural fracture. Abstract: Rock mass containing natural fractures is susceptible to freeze-thaw (F-T) weathering in cold regions and could result in the instability of rock engineering and even serious geological hazards. Yet the F-T action on the change of fracture physical characteristics and the associated fracturing evolution of naturally fractured rock is poorly understood. In this work, multi-level compressive cyclic loading experiments were performed to investigate the fracture evolution of naturally fractured granite using real time acoustic emission monitoring and post-test CT scanning. The results show that the aperture change of natural fracture is related to the fracture openness and filling characteristics, the open-type fracture is sensitive to F-T treatment and its aperture increases faster than the close-type and fill-type fractures. In addition, the stress strain curve pattern is impacted by the initial natural fracture volume. The AE activities at fatigue loading stage are weaker than the stress-increasing stage. The proportion of low frequency AE signals increases with increasing natural fracture volume, and the shear-sliding along natural fracture results in the occurrence of low-frequency signals. Moreover, interactions between the natural fracture and stimulated new fracture are visualized using CT scanning and it is found that the initial natural fracture volume impacts the failure mode and fracture network pattern. The testing results are expected to improve the understanding of the influence of natural fractures on rock damage and deformation in cold regions.